Simultaneous determination of hydrochlorothiazide, amlodipine besylate and olmesatan medoxomil in tablets by high performance liquid chromatography - Le, Thi Dieu Huyen; Duong, Van Tho; Phan, Anh Tu; Nguyen, Thi Ngoc Dung; Phan, Thanh Dung (Tạp chí Y Dược Huế, 2024)
Background: The combination of hydrochlorothiazide (HCT), amlodipine besylate (AML) and olmesartan medoxomil (OLM) is highly effective in treating hypertension. Currently, Vietnamese Pharmacopoeia V and other reference pharmacopoeias do not have a procedure for the simultaneous quantification of these three ingredients. Objective: To develop and validate a procedure for simultaneous determination of HCT, AML and OLM in tablets by HPLC method. Materials and method: Materials: tablets containing three ingredients HCT, AML and OLM. Method: Investigation of chromatographic conditions, including mobile phase compositions and elution mode, development and validation of a procedure for simultaneously quantifying HCT, AML and OLM in tablets using the HPLC method according to ICH guidelines and the Drug Registration Manual, appendix 8. Results: The reversed-phase high-performance liquid chromatography method was developed with chromatographic conditions: column Xterra® C18 (250 × 4.6 mm; 5 μm), PDA detector with detection wavelength 237 nm, column temperature 30 °C, flow rate 1 ml/min, sample injection volume 10 μl, gradient elution with mobile phase acetonitrile – triethylamine buffer pH 3. Results showed that these compounds were completely separated, the retention time of HCT, AML, OLM were 5.127 minutes, 9.279 minutes and 12.889 minutes, respectively. The procedure has been validated and has met the requirements about system suitability, specificity, accuracy, precision, linearity, robustness. Conclusion: A procedure for simultaneously quantifying these three compounds in tablets using the HPLC method has been successfully developed and validated.